Building affective commitment through job characteristics, leadership and empowerment. (9th February 2015) - Pentareddy, Sandhya; Suganthi, L.
Abstract: Employees committed to their organizations are more likely to contribute better and remain longer with their companies. This study examines how to build such organizational commitment through job characteristics, leadership and empowerment. Using a sample of 605 knowledge workers from four countries and various industries, this study probes how leadership complexity and psychological empowerment transform the impact of job characteristics on affective commitment. Results indicate that psychological empowerment partially mediates the effects of job characteristics on affective commitment and that leadership complexity moderates the influence of job characteristics and empowerment on affective commitment. Theoretical and practical implications of the research findings are discussed